PENINGKATAN PEMAHAMAN KARYA TULIS ILMIAH BAGI SISWA MADRASAH ALIYAH MIFTAHUL ANWAR - Mubarok, Muhammad Syauqi; Waldy Kariman, Mikyal; Salam, Fitriyadi; Silcilia, Putri; Fiqri Muzahidat, Sahrudin; Faruk Romdoni, Sayyid; Rahmat, Agil; Ridwan Firdaus, Muhammad; Fahmi Assidiq, Muhammad; Saptahadi Ilmasik, Heryaman; Esa Saputra, Rizki; Subarkah, Adie; Nurhasna Fauziyah, Rizma; Ramadhan, Syahrul; Beni Okta Sari, Cantika; Idris Purnama, Fahmi; Ezar Benandika, M. Rizq; Zayin, Repin; Mu’min, Mu’min; Sungkono Nanda Putra, Aditya; Zulfa Faiha, Hafiz (Institut Teknologi Garut, 2023)
Scientific writing is one of the important aspects in the world of education to determine graduation. Lack of understanding regarding scientific writing is the main problem for students in writing scientific writing. To overcome this problem, teaching activities carried out by the KKN team can be a solution in increasing students' understanding of scientific writing. The learning method used is to use Contextual Teaching and Learning. This learning method is able to increase students' understanding of scientific writing. In the teaching activities carried out, the learning results showed that there was an increase in students' understanding as indicated by the exam results of 83.72% of the questions given to students related to scientific papers being answered correctly.